The use of conversation fillers in English by Indonesian EFL Master's students - Fitriati, Sri Wuli; Mujiyanto, Januarius; Susilowati, Endang; Akmilia, Perwari Melati (Linguistic research, 2021)
Fillers can be beneficial for English as a foreign language (EFL) learners and have many functions. Although fillers are useful in spontaneous speaking, some learners have not been aware of how and when to use fillers in spoken communication. Some research studies investigated the use of fillers by EFL learners, but none has focused on a casual conversation in English. This article reports on a study that aims at investigating and examining the types and functions of fillers produced by Master's students of English as a foreign language (henceforth, EFL Master's students). This group of learners is at the advanced level of English language learners, so it is necessary to look at their oral communication skills, such as casual conversations because this type of communication is relatively not easy for learners to engage. This is a qualitative case study that employs a conversation analysis. The participants are at a state university in Semarang, Indonesia. The data were collected from audio recordings which were then transcribed. The transcriptions were analyzed by using Rose's (1998) theory of types of fillers and Stanstrom's (1994) theory of functions of fillers. The findings reveal that: (1) the students frequently used lexicalized fillers, followed by unlexicalized ones. The dominant lexicalized filler is so, whereas the dominant unlexicalized filler is emm, and (2) Fillers produced by the students function as hesitation, empathizer, mitigation, time-creating devices, and editing term. The findings are further discussed with the theory of communicative competence. Finally, this article presents some pedagogical implications of this study on teaching speaking to learners of English as a foreign language.